A experiência de psicólogos que exercem sua ação clínica numa perspectiva fenomenológica existencial - Cabral, Maria Danielly da Silva (2009)
This research intends to comprehend the experience of psychologists who develop the existential phenomenological perspective in their clinical activity and holds up specific objectives as describing the trajectory of the academic and professional process until the choice of existential phenomenological approach. It also tries apprehend the existential phenomenological assumptions that lead the clinical activity of these psychologists and understand how psychologists who take this view realize their possibilities and limits. The methodology is focused on a clinical intervention with a qualitative approach. The instrument of the research will be held through psychologists testimonials (collaborators characters). The narratives, based on Benjamin and Schmidt as a possibility of life experience, are undergone subject to further to analytical sense proposed by Critelli as a procedure investigation and phenomenological analysis. The results showed that all interviewed based on a dissatisfaction of what was offered to them, in a quiet or more intense way, slowly or suddenly, they felt themselves more deeply taken by the prospect of their choice. The sensation of a meeting, lived through great emotion, marked each one of the narrators that despite the passage of time brought with great liveliness and freshness the lived moment from their lives. Lives, existences that have felt in harmony, integrity, coherency, speaking about their points of views, man s view, as they strongly emphasized at the prospect of clinical activity of existential phenomenology. The requirement for a professional choice is deeply intertwined with the history of each one, that was really the fact of their motivation. In our region, the existential phenomenological conception was introduced by contemporary psychologies that promoted existential humanist ideals. All of the interviewed identified themselves with this perspective. Themes to this movement were often cited as essential during the action of our collaborators characters: freedom-responsibility, singularity, multiplicity, clinical and empathy listening , sense, meaning, openness to new, anguish and death. However, except for one of our interviewed, who considering himself into the transition process, and due this particular moment, shows critically the conceptions of several authors and movements of the highlighted field. The other ones openly associate existential concepts of humanism with the analytical existence. The certainly of the correct choice, and the satisfaction with the clinical effort offered different ways to the interviewed group. Certainly, it is through this mood that they assessed the limits of their own clinical activity. So, in a general way, they believe that the difficulties are related to inadequacy of the professionals, that is, the difficulties may be linked to their own history, to the examination of themselves or to the deep learning of the concepts proposed by existential phenomenology